Cover Feature: Enabling High Lithium Conductivity in Polymerized Ionic Liquid Block Copolymer Electrolytes (Batteries & Supercaps 2/2019). Issue 2 (28th January 2019) - Goujon, Nicolas; Huynh, Tan‐Vu; Barlow, Kristine j.; Kerr, Robert; Vezzù, Keti; Di Noto, Vito; O'Dell, Luke A.; Chiefari, John; Howlett, Patrick C.; Forsyth, Maria
Abstract : The Cover Feature illustrates the use of a polymerized ionic liquid block copolymer as the polymer host for high energy density lithium metal batteries. The macrophase separation present in these electrolytes provides the mechanical integrity required for lithium dendrite suppression whilst promoting high lithium conductivity pathways through the use of an ionic liquid additive. More information can be found in theCommunication by N. Goujon et al. .